How does interpersonal communication affect health and patient safety - DERMAN, GİRAY SAYNUR (My University, 2020)
Effective health and safety communication is one of the building blocks of organizational health and safety culture. Patient safety is compromised by medical errors and adverse events related to miscommunications among healthcare providers. The most important element defining the culture of health and safety in the organization is how health and safety are discussed between employees and managers, from meeting rooms to breaks. Communication among health service providers is influenced by human factors such as interpersonal relations. However, interpersonal relations and communication debates are lacking in the medical team literature. This paper proposes a theoretical framework that explains how interpersonal relations among healthcare team members affect communication and team performance, such as patient safety, and health. In this study, how various communication styles affect the health and safety environment in the enterprise is discussed and the effect of empathic communication on organizational health safety culture and performance is discussed.
Keywords: Interpersonal communication; health; professional teamwork; empathic communication; patient safety; leadership